2017
DOI: 10.1002/cptc.201600042
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Reactivity Patterns in Light‐Induced Nitrile Imine Mediated Tetrazole–Ene Cycloadditions

Abstract: A rationale for predicting photochemical tetrazole activation in the popular nitrile imine mediated tetrazole–ene cycloaddition (NITEC) reaction, based on a combined theoretical and experimental study, is reported. DFT calculations of three tetrazole derivatives reveal that the efficiency of intersystem crossing is determined by the chromophore moiety. This species is critical in dictating the reactivity of the tetrazoles towards nitrile imine formation, yet mere inspection of the chromophore moiety's absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…Thus, the observed conversion values after excitation with 285 nm and 292 nm light evidence that the NITEC reaction proceeds with a remarkably high efficiency in this wavelength regime, the minimum quantum yield at 285 nm is estimated as 0.55 ± 0.06. A correlation with an excitation into the S1 state with a potentially very efficient intersystem crossing into the T3 state, which was previously estimated as having a relative energy of DGT3 = 406 kJ mol -1 (4.21 eV, 295 nm), 59 is proposed here. We reported that the tetrazole B1 has a vertical S1 state close to the T3 state and can thus be expected to exhibit a fast ISC.…”
Section: Wavelength Dependence Of Nitrile Imine Mediated Tetrazole Enmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, the observed conversion values after excitation with 285 nm and 292 nm light evidence that the NITEC reaction proceeds with a remarkably high efficiency in this wavelength regime, the minimum quantum yield at 285 nm is estimated as 0.55 ± 0.06. A correlation with an excitation into the S1 state with a potentially very efficient intersystem crossing into the T3 state, which was previously estimated as having a relative energy of DGT3 = 406 kJ mol -1 (4.21 eV, 295 nm), 59 is proposed here. We reported that the tetrazole B1 has a vertical S1 state close to the T3 state and can thus be expected to exhibit a fast ISC.…”
Section: Wavelength Dependence Of Nitrile Imine Mediated Tetrazole Enmentioning
confidence: 95%
“…The relative energy of the optimized S1 state was reported earlier as DGS1, opt = 384 kJ mol -1 (3.98 eV, 312 nm). 59 Reactivity at 322 nm, relating to an activation of the tetrazole with photons not carrying sufficient energy to excite into the S1, according to aforementioned quantum chemical calculations, can thus be explained by a vibrational energy contribution to the excitation. Given that the triplet state is a crucial intermediate in the NITEC reaction, 59 further quantum chemical calculations were performed with the aim to arrive at a complete picture of the reaction path (refer to Figure 7).…”
Section: Wavelength Dependence Of Nitrile Imine Mediated Tetrazole Enmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to keep the modified nucleotide as small as possible the uracil moiety replaces one of the aryl groups of conventional diaryltetrazoles. The bromo substituent at the opposite aryl group is needed for efficient photoclick chemistry [19] presumably by its heavy-atom effect on populating the photochemically active triplet state [22]. The synthetic route (Scheme 1) was adapted from the synthesis of a similar 2 -deoxyuridine building block for DNA recently published by our group [19] but contains improved synthetic procedures and a different protection scheme due to the presence of the 2 -hydroxy group.…”
Section: Resultsmentioning
confidence: 99%
“…Nitro‐substituted hydrazone 3s and analogous derivatives 3t and 3u were all accessed in good to acceptable yields. These compounds represent examples of substrates incompatible with the route previously developed in our laboratory, due to the very limited photochemical reactivity of the relevant nitro‐substituted tetrazole precursors . Alkyl substitution of the NI, which was similarly unsuited to the initial UV‐promoted protocol, was also accomplished (c.f.…”
Section: Resultsmentioning
confidence: 99%